PENGARUH LATIHAN MULTIBALL TERHADAP PENINGKATAN PUKULAN BACKHAND PADA PERMAINAN TENIS MEJA SPARTA UNIVERSITAS NEGERI MAKASSAR - Hasnah Hasnah; A Masjaya AM; Hezron Alhim Dos Santos; Maria Herlinda Dos Santos; Merianti Ansar (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2023)
The results of this study aim to see the role of multiball how much it increases backhand stroke skills in table tennis and how the role of multiball exercises is to improve backhand stroke skills in table tennis games. The research was conducted by random sampling to a population of all Sparta athletes, totaling 45 people. Data collection using the method of test and measurement techniques. The test instrument used is multiball to determine the effect of multiball training. The variables in this study include Multiball as the independent variable, as well as improving backhand skills as the dependent variable. The data analysis technique uses descriptive analysis techniques and inferential analysis through the SPSS.22 program with a significance level of 95% (α = 0.05)The results of the research analysis show that: (1) multiball training is proven to increase backhand shots with a contribution of 64.5%;(2) The multiball training group has a greater effect on increasing backhand strokes than the control with an increase in out shuffle-plyo push ups of 12.85% of the average pretest carried out before treatment with an average posttest, while for the control it is only 3.9 % of the average pretest and posttest scores.